2010
DOI: 10.1148/radiol.10100303
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Mycobacterial Disease: Diagnostic Performance of Low-Dose Digital Tomosynthesis as Compared with Chest Radiography

Abstract: DTS performed with a low-dose technique is superior to radiography for the detection of lung lesions in patients with pulmonary mycobacterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 21 publications
2
42
0
6
Order By: Relevance
“…24,25,27 Also, several studies demonstrated the effective dose of each modality for standard patient in each study protocol, [9][10][11][12]21 and we found that the radiation dose for DTS was approximately twice that for chest radiography and DTS required a much smaller radiation dose in comparison with CT.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…24,25,27 Also, several studies demonstrated the effective dose of each modality for standard patient in each study protocol, [9][10][11][12]21 and we found that the radiation dose for DTS was approximately twice that for chest radiography and DTS required a much smaller radiation dose in comparison with CT.…”
Section: Discussionsupporting
confidence: 52%
“…9,11,13,[21][22][23] However, we could extract the total numbers of true positives and the total number of pulmonary nodules, which allowed us to calculate and analyze detection rates. Thus, we identified 7 studies (1017 patients) that presented per-patient results 10,12,[17][18][19][20][21] and 10 studies that presented per-lesion results (2159 lesions) 9,11,13,[21][22][23][24][25][26][27] for meta-analysis. Only one study included both per-patient-and per-lesion-based data.…”
Section: Study Characteristics and Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the tissue overlap problem of chest radiography while exposing the patient to only a slightly higher radiation dose as compared with chest radiography. [8][9][10] In comparisons with chest radiography, DTS has been shown to substantially increase the detection of pathology such as pulmonary nodules, 5,[11][12][13][14][15] mycobacterial disease, 16 pleuropulmonary disease, 17 and pulmonary emphysema. 18 The clinical interest has also been based on the successful use of DTS as a problem-solving tool after chest radiography, [19][20][21] substantially reducing the need for CT after a non-conclusive chest radiography.…”
Section: Introductionmentioning
confidence: 99%
“…igital tomosynthesis has been applied to a variety of applications, including breast imaging (1-3), orthopedic imaging (4-8), urologic imaging (9), and chest imaging (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Digital chest tomosynthesis has been available and cleared by the U.S. Food and Drug Administration since 2006.…”
mentioning
confidence: 99%